Study on the Corrosion Evolution and Mechanical Properties of Q420qENH Weathering Steel in Marine Atmospheric Conditions - CHENG Haigen, ZOU Peng, ZHENG Shangmin, GONG Hanlong, WU Tianwen (Cailiao Baohu)
With the continuous development of weathering steel in the field of bridges in recent years，there have been numerous cases of weathering steel being used without coating， but the service environment for weathering steel needs to be studied， especially in the complex environment such as highly corrosive marine atmosphere.Therefore， taking Q420qENH steel used in the Zangmu Yarlung Zangbo River extra-large bridge as the research object， the marine atmospheric corrosion environment was simulated using an electrolytic accelerated corrosion test.The corrosion behavior of Q420qENH in this environment and the reduction in the mechanical properties of the weathering steel base metal and its butt joint after corrosion were investigated.Based on the corrosion kinetics， morphology evolution of the rust layer， phase composition， the acceleration effect of the electrolytic corrosion test， and the reduction in mechanical properties， a multi-angle comprehensive analysis was conducted.Results showed that the corrosion rate of Q420qENH in the marine atmosphere increased initially and then decreased.The weathering steel primarily relied on Fe3O4 to form a thick， slightly dense rust layer， which prevented direct erosion of the substrate by water， oxygen and pollutants in the atmospheric environment.However， the surface rust layer was loose and porous， limiting its ability to prevent the invasion of corrosive media.Additionally， it was difficult for Q420qENH to form a dense surface rust layer in the marine atmospheric corrosion environment.The corrosion grade was between C3 and C4， and it was concluded that Q420qENH was unsuitable for coating-free use in such environments.In terms of mechanical properties， the degrees of reduction in yield strength， tensile strength and elongation of the base metal of the weathering steel and its butt joint after 4，8 and 14 h of corrosion gradually increased compared to those without corrosion.However， after 14 h of accelerated corrosion， the yield strength and tensile strength remained above 360 MPa and 466 MPa， respectively， with the mechanical strength still at a high level.